2012
DOI: 10.1590/s0102-695x2012005000030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro and in vivo anticancer properties of Moroccan propolis extracts

Abstract: This investigation aimed to evaluate the in vitro and in vivo antitumor potential of a Moroccan propolis extracts. For in vitro assays, three mammalian tumor cell lines were used: BSR (hamster renal adenocarcinoma), Hep-2 (human laryngeal carcinoma) and P815 (murin mastocytoma). The propolis ethanolic extract as well as the ethyl acetate extract, exert an in vitro cytotoxic activity in dose-dependent manner. The IC50 values were ranging from 15 µg/mL to 38 µg/mL. This activity depends not only on the extract's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…[27] [28] Briefly, cells were washed twice with PBS at a density of 1.5 9 10 5 cells/ml in flat-bottomed 96-well microtiter plates (Thermo Fisher Scientific) in 100 ll per well of complete medium. The used cell lines were obtained from the Biological Resource Center of Gustave Roussy Institute, Villejuif, France as a gift of Prof. G. Lemaire, Institute of Biochemistry, University of Paris XI, France.…”
Section: Cytotoxic Activity Assaymentioning
confidence: 99%
“…[27] [28] Briefly, cells were washed twice with PBS at a density of 1.5 9 10 5 cells/ml in flat-bottomed 96-well microtiter plates (Thermo Fisher Scientific) in 100 ll per well of complete medium. The used cell lines were obtained from the Biological Resource Center of Gustave Roussy Institute, Villejuif, France as a gift of Prof. G. Lemaire, Institute of Biochemistry, University of Paris XI, France.…”
Section: Cytotoxic Activity Assaymentioning
confidence: 99%
“…Many biological properties have been attributed to propolis, including anticancer (Mouse et al, 2012), antimicrobial (Popova, Silici, Kaftanoglu, & Bankova, 2005), antioxidant (Alves & Kubota, 2013), antileishmanial (Duran, Muz, Culha, Duran, & Ozer, 2011), wound healing (Batista et al, 2012;Guney, Karaman, Oner, & Yerer, 2011), anti-inflammatory and immunomodulatory activities (Araujo, Libério, Guerra, Ribeiro, & Nascimento, 2011). For example, Mouse et al (2012) investigated the chemical composition of Moroccan propolis extracts by HPLC/ESI-MS, as well as their in vitro and in vivo anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mouse et al (2012) investigated the chemical composition of Moroccan propolis extracts by HPLC/ESI-MS, as well as their in vitro and in vivo anticancer potential. It was shown that Moroccan propolis extracts contained several flavonoids, including rhamnetin, luteolin, and trihydroximethoxiflavone, some flavonoid glucosides, such as wogonoside, quercetin arabino-glucoside, and kaempferol O-glucoside and that the anticancer activity depended mainly on not only the chemical composition of the extracts, but also on the target tumor cells (Mouse et al, 2012). Using a GC-MS based approach, Duran et al (2011) investigated the relationship between the chemical composition extracts obtained from two Turkish propolis and their antileishmanial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have found similar results as [255] for propolis from Algeria, which showed immunomodulatory and anti-inflammatory effect in animals with uveitis induced by α-tropomyosin. [293] Mouse et al [120] did a screening of the antitumor potential of Moroccan propolis extracts, from Beni Mellal region, in P815 tumor-bearing mice and have found that the treatment with propolis have the capacity to reduce the tumor volume as compared with the control. [120] Mountassir et al [294] have investigated samples from the same region regarding its possible antinociceptive activity and have conclude that propolis activated both central and peripheral mechanisms to elicit the analgesic effect in tested animals.…”
Section: Application In Medicine Pharmacy and Bio-allied Sciencementioning
confidence: 99%